Are you open? a content analysis of transparency and openness guidelines in hci journals - Ballou,N; Warriar,VR; Deterding,S (2021)
Within the wider open science reform movement, HCI researchers are actively debating how to foster transparency in their own feld. Publication venues play a crucial role in instituting open science practices, especially journals, whose procedures arguably lend themselves better to them than conferences. Yet we know little about how much HCI journals presently support open science practices. We identifed the 51 most frequently published-in journals by recent CHI frst authors and coded them according to the Transparency and Openness Promotion guidelines, a high-profle standard of evaluating editorial practices. Results indicate that journals in our sample currently do not set or specify clear openness and transparency standards. Out of a maximum of 29, the modal score was 0 (mean = 2.5, SD = 3.6, max = 15). We discuss potential reasons, the aptness of natural science-based guidelines for HCI, and next steps for the HCI community in furthering openness and transparency.